Korporasi Sebagai Subjek Hukum dan Pertanggung-Jawabannya dalam Hukum Pidana Indonesia - Ragil Surya, Prakasa; Pratiwi, Intan; Utari, Dian; Prima, Annisa Belva; Amerta, Muhammad Rovi (ASOSIASI IDEBAHASA KEPRI, 2024)
A corporation is a business entity whether as a legal entity or not a legal entity, but within it there is an organizational management structure and runs its business through its management.This research focuses on three problems, namely how corporations are defined, what the subject of criminal law is like in Indonesia, and what the position of corporations are as subjects of criminal law and their responsibilities in criminal law in Indonesia. This research uses normative research methods which refer to research and literature related to the problems studied. This research concludes that the position of corporations in criminal justice also varies. These positions include the following: (1) as the author of a criminal act, (2) as a tool for committing a criminal act, (3) as the object of a criminal act. The concept of criminal law regarding corporate responsibility is experiencing development. Models of corporate responsibility as time goes by, namely: (1), legal fiction theory, (2) ultra virez doctrine, (3) identification theory, (4) strict liability, (5) vicorious liability, (6) successful liability, (7) delegation theory.